Investigation of the Large-scale Neutral Hydrogen near the Supernova Remnant W28 - Velázquez, P. F. (2002)
The distribution and kinematics of neutral hydrogen have been studied in a wide area around the supernova remnant (SNR) W28. A 2fdg5 × 2fdg5 field centered at l = 6fdg5, b = 0° was surveyed using the Parkes 64 m radio telescope (half-power beamwidth of 14farcm7 at λ21 cm). Even though W28 is located in a complex zone of the Galactic plane, we have found different H I features, which are evidence of the interaction between W28 and its surrounding gas. An extended cold cloud with about 70 M⊙ of neutral hydrogen was detected at the location of W28 as a self-absorption feature, near the local standard of rest velocity of +7 km s-1. This H I feature is the atomic counterpart of the molecular cloud shown by previous studies to be associated with W28. From this detection, we can independently confirm a kinematical distance of about 1.9 kpc for W28. In addition, the neutral hydrogen observed in emission around the SNR displays a ringlike morphology in several channel maps over the velocity interval [-25.0, +38.0] km s-1. We propose that these features are part of an interstellar H I shell that has been swept up by the supernova shock front. Emission from this shell is confused with unrelated gas. Hence, we derive an upper limit for the shell mass of 1200–1600 M⊙, a maximum radius of the order of 20 pc, an expansion velocity of ~30 km s-1, an initial energy of about 1.4–1.8 × 1050 ergs, and an age of ~3.3 × 104 yr. The preexisting ambient medium has a volume density on the order of 1.5–2 cm-3. W28 is probably in the radiative evolutionary phase, although it is not possible to identify the recombined thin neutral shell expected to form behind the shock front with the angular resolution of the present survey.